Wallace Stevens - Sharpe, T. author. aut Link
XIII, 220 p.
Keywords: Tony Sharpe explores the symbiotic and antagonistic relations between Stevens's literary life and his working life as insurance executive, outlining the personal, historical and publishing contexts that shaped his writing career, and suggesting how awareness of these contexts throws new light on the poems. In this appreciative but not uncritical study, Sharpe tries to see the man behind the mandarin, whilst remaining alert to the challengingly sumptuous austerities of one of America's most significant poets.